2012
DOI: 10.1371/journal.pone.0031711
|View full text |Cite
|
Sign up to set email alerts
|

Collective Motion of Cells Mediates Segregation and Pattern Formation in Co-Cultures

Abstract: Pattern formation by segregation of cell types is an important process during embryonic development. We show that an experimentally yet unexplored mechanism based on collective motility of segregating cells enhances the effects of known pattern formation mechanisms such as differential adhesion, mechanochemical interactions or cell migration directed by morphogens. To study in vitro cell segregation we use time-lapse videomicroscopy and quantitative analysis of the main features of the motion of individual cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 28 publications
6
90
3
Order By: Relevance
“…This is qualitatively in agreement with the scaling reported from experiments. Méhes et al [7,43] studied the kinetics of cell sorting in mixtures of keratocytes from various species. For mixtures of primary fish keratocytes and EPC keratocytes, the interface index g and the growth of homotypic clusters were approximately linear on a log -log scale (over one decade of data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is qualitatively in agreement with the scaling reported from experiments. Méhes et al [7,43] studied the kinetics of cell sorting in mixtures of keratocytes from various species. For mixtures of primary fish keratocytes and EPC keratocytes, the interface index g and the growth of homotypic clusters were approximately linear on a log -log scale (over one decade of data).…”
Section: Discussionmentioning
confidence: 99%
“…Such cell sorting has also been observed for dissociated Hydra cells, co-cultures of cells not in contact during normal development and mixtures of cells extracted from different species [4][5][6][7].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For instance, culture volume and cell density can be important factors when establishing biomimetic in vitro models. In a study investigating the embryonic developmental processes segregation and pattern formation, cell number in the co-culture was chosen to be comparable in size to an embryo, so that it was relevant to the natural biological system [83]. In biotechnology, there are two opposing forces in the scaling of experimental volumes: efforts to scale up experiments to industrial volumes and yields, and efforts to scale down experiments to the microlitre scale to allow high-throughput testing of different systems or conditions and also for point-of-care or in-the-field applications [96].…”
Section: Volume Of Co-cultures: Reporting Standards To Enhance Progressmentioning
confidence: 99%
“…In 2-dimensional co-cultures of adherent cells on a rigid substrate Méhes et al (2012) studied the dynamics of segregation of two initially mixed cell populations into distinct clusters by cell migration in an environment lacking pre-defined external cues. They have found that segregation into large multicellular clusters is facilitated by collective effects in cell motion such as an increase in the directional persistence of constituent cells.…”
Section: Two-dimensional Segregation: Pattern Formation On a Substratementioning
confidence: 99%